2013
DOI: 10.1105/tpc.113.118158
|View full text |Cite
|
Sign up to set email alerts
|

MAIGO5 Functions in Protein Export from Golgi-Associated Endoplasmic Reticulum Exit Sites inArabidopsis 

Abstract: Plant cells face unique challenges to efficiently export cargo from the endoplasmic reticulum (ER) to mobile Golgi stacks. Coat protein complex II (COPII) components, which include two heterodimers of Secretory23/24 (Sec23/24) and Sec13/31, facilitate selective cargo export from the ER; however, little is known about the mechanisms that regulate their recruitment to the ER membrane, especially in plants. Here, we report a protein transport mutant of Arabidopsis thaliana, named maigo5 (mag5), which abnormally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 85 publications
(133 reference statements)
1
57
0
Order By: Relevance
“…1E). The observation on the association of AtSar1a punctate with the Golgi apparatus is consistent with previous studies using superresolution microscopy that showed that ERES are surrounded by the Golgi apparatus and that ERES shows more numbers than the Golgi (15,23). In contrast, most of the AtSar1c-GFP-labeled punctae were not Golgi-associated under superresolution microscopy.…”
Section: Resultssupporting
confidence: 80%
“…1E). The observation on the association of AtSar1a punctate with the Golgi apparatus is consistent with previous studies using superresolution microscopy that showed that ERES are surrounded by the Golgi apparatus and that ERES shows more numbers than the Golgi (15,23). In contrast, most of the AtSar1c-GFP-labeled punctae were not Golgi-associated under superresolution microscopy.…”
Section: Resultssupporting
confidence: 80%
“…With the exception of Sec13, which has also been found at the nuclear envelope (Yang et al, 2005), Sec23, Sec24, and Sec31 are predominantly localized at such areas. Three-dimensional projection reconstruction of confocal images followed by rendering analyses have shown that Sec16 is localized in cup-like structures where the ER assumes a high-degree curvature (Takagi et al, 2013;Fig. 2), supporting the intriguing possibility for specific requirements of ER membrane curvature for the ERES establishment and maintenance.…”
Section: Federica Brandizzi: the Secretory Units Model For Er Proteinmentioning
confidence: 97%
“…In live-cell imaging analyses, the Arabidopsis (Arabidopsis thaliana) COPII coat components (Sec13, Sec23, Sec24, and Sec31), when expressed in highly vacuolated leaf epidermal cells in tobacco (Nicotiana tabacum) and Arabidopsis, have been found in punctate structures that are associated with the ER and move with the Golgi stacks (Stefano et al, 2006;Hanton et al, 2007Hanton et al, , 2009Sieben et al, 2008;Wei and Wang, 2008;Faso et al, 2009;Takagi et al, 2013;Tanaka et al, 2013), which, in fully expanded plant cells, are highly dispersed and motile (Boevink et al, 1998;Stefano et al, 2014). The punctae labeled by the COPII coat proteins are commonly indicated as ER exit sites (ERESs).…”
Section: Federica Brandizzi: the Secretory Units Model For Er Proteinmentioning
confidence: 99%
“…Zelazny et al, 2009;Sorieul et al, 2011). SECRETION-ASSOCIATED AND RAS-RELATED 1 (SAR1), a Ras-like small GTP-binding protein, also appears to function in COPII vesicle assembly in plants, and plant orthologs of further constituents of COPII-coated vesicles, selective vesicle budding and cargo export from the ER have been identified (Bar-Peled and Raikhel, 1997;Osterrieder et al, 2010;Montesinos et al, 2012;Takagi et al, 2013). This is also true for elements of COPI-mediated retrograde transport, which mediates sorting back to the ER (Donohoe et al, 2007).…”
Section: General Aspects Of Early Secretory Sorting Eventsmentioning
confidence: 99%